Deformation Localization and Damage Constitutive Model of Raw Coal and Briquette Coal under Uniaxial Compression. (27th January 2022) - Ge, Lina; Yi, Fu; Du, Changbo; Zhou, Junxia; Cui, Zhenglong; Wang, Tao
Abstract : In order to compare and analyze the difference in deformation and damage law of soft and hard porous media materials, the digital image correlation is used to evaluate the heterogeneous development of strain fields of hard and brittle raw coal material and soft plastic briquette coal material under uniaxial compression. Through the defined statistical indicator, the quantitative characterization of deformation localization is realized, and the material damage constitutive model based on the statistical indicator of strain field is established. The results show that the yield stage of raw coal is not obvious, showing the characteristics of strain hardening and X-shaped macroscopic shear failure. The yield stage of briquette coal is more obvious, showing the characteristics of strain softening and a tensile failure mode. The progress of strain localization can well reflect the damage and destruction process of materials. The progress of strain localization of briquette coal can be divided into uniform deformation stage, localization stage, and failure stage, while the stage characteristics of localized evolution of raw coal is not obvious. The theoretical results of the damage constitutive model defined by statistical indicator are in good agreement with the experimental data and can well reflect the stress and strain characteristics of the two materials.